Examining the unique contributions of parental and youth maltreatment in association with youth mental health problems. (February 2022) - Khoury, Jennifer E.; Tanaka, Masako; Kimber, Melissa; MacMillan, Harriet L.; Afifi, Tracie O.; Boyle, Michael; Duncan, Laura; Joshi, Divya; Georgiades, Katholiki; Gonzalez, Andrea
Abstract: Background: Extensive research seeks to understand the intergenerational impact of child maltreatment. However, it remains unclear how parent's history of child maltreatment (PCM) is associated with child mental health, after accounting for children's experiences of maltreatment and other proximal risk factors. Objective: This study examines the associations between PCM and youth internalizing and externalizing problems, while accounting for youth experiences of maltreatment (YM), and parent mental health and positive parenting. Participants and setting: Youth aged 14 to 17 years ( N = 2266) participated in the 2014 Ontario Child Heath Study. Methods: Parents and youth reported their experiences of child maltreatment. Parent-report and self-reports of youth internalizing and externalizing problems were also collected. Number of subtypes of maltreatment and specific subtypes of maltreatment were examined. Parents reported their own mental health problems and positive parenting practices. Results: Regarding number of maltreatment subtypes, initially PCM was associated with parent-reported, but not self-reported, youth internalizing and externalizing problems. After accounting for YM, parent mental health problems and positive parenting, only YM remained significant. Regarding specific subtypes of maltreatment, both parent and youth emotional abuse were related to parent- and youth-reported internalizing and externalizing problems, after controlling for other maltreatment subtypes. However, the effects of parent emotional abuse became nonsignificant after accounting for YM and proximal risk factors. Conclusions: Findings indicate: 1) the unique associations between specific PCM and YM subtypes and youth mental health problems; 2) the role of proximal risk factors in explaining the association between PCM and youth mental health; and 3) the importance of multiple informants of youth mental health problems.